Grenada. Significant achievements 2018 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
The main activities carried out by the Institute in Granada during 2018 are identified, with respect to the needs and interests of the country, strengthening issues such as governance, beekeeping, biosecurity, food safety, use of organic fertilizers and composting of alternative materials, such as Sargassum algae. Likewise, work was done to improve methodologies, post-harvest management, management of shade houses and management of slaughterhouses. In addition, disease prevention and pest control, such as citrus greening disease, was supported. Finally, the extension of the useful life of local fruits and vegetables was implemented, as well as improving the health of the soil.